Hubungan Self Efficacy dengan Student Engangement pada Siswa SMPN 1 Biru-Biru - Yulia, Anggreni; Hafni, Merri (Jouska: Jurnal Ilmiah Psikologi, 2024)
This article aims to determine the correlation This research aims to find out how the correlation between self-efficacy and student engagement at SMP N 1 Biru-biru. Self-efficacy is the belief that an individual can develop abilities and beliefs to produce good work results from effort and motivation within the individual. Student engagement is the involvement of students in activities at school both academically and non-academically The research population consisted of 288 students from grades 1-3 of junior high school and 167 research samples were taken using the random sampling method. This study used two psychological scales, namely the self-efficacy scale and the student engagement scale using the Likert scale model. The results of this study show a correlation coefficient of rxy = 0.955 with p = 0.000 (p0.050), meaning that there is a positive correlation between self-efficacy and student engagement. With these results, the hypothesis in this study that there is a positive correlation between self-efficacy and student engagement is accepted. The value of the correlation coefficient indicates that there is a correlation between two variables. Self-efficacy made an effective contribution because it is only 91.1%. The mean empirical variable of self-efficacy obtained is 127.43 while the mean empirical of student engagement is 117.69 then the hypothetical mean of self-efficacy variable is 97.5 and the mean hypothetical variable of Student engagement is 85.